(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
Nowadays, many hotel operators and homestay owners(host)advertise their assets for short-term accommodation through digital platforms in search of a wider market while offering positive options for customers in terms of its compatible prices and variety of choices. However, the recent Movement Control Order (MCO) declared by the Malaysian Government to control the spread of the COVID-19 pandemic has affected Malaysia’s tourism industry. This had caused concern on the effect of the existing contracts entered by hosts and the guests via digital platforms as it was impossible for the parties to perform their contract, especially when the customers had made full payment of the bookings. Though MCO’s effect has contributed great financial loss to the digital platforms and the hosts, the guests also suffered a loss due to the travel restriction and the money they have paid for the travel. Many hosts argued that since the MCO was an abrupt announcement from the government, they have discretionary power not to grant cancellation of booking since the contract’s performance becomes impossible. Additionally, the digital platforms have provided terms or policies concerning the refund of payments, which applies to certain circumstances and the procedures stated in the platforms’ policy statement. Thus, this article will analyse the legal effect of the frustrated contract with special reference to a booking made via digital platform before MCO and discuss the nature of the doctrine of frustration and force majeure in the contract law. The authors will adopt doctrinal and statutory analysis. Its findings will highlight the scope and effect of the doctrine of frustration in contracts entered with homestay owners via Malaysia’s sharing economy platform.